Usage of Azolla in livestock farming - Khojaeva Nasiba; Kirikchi Koray; Ummatov Utkir; Khojiakhmatov Sobitkhon; Yelibayeva Sevara (BIO Web of Conferences)
In modern cattle farming, an important task is optimizing the feed base to enhance production efficiency. One of the promising directions is the use of aquatic plants, such as Azolla, which has high nutritional value. This article examines the impact of Azolla on the productivity of cattle, including their growth, development, milk productivity, and health. The results of experiments with the addition of Azolla to feed mixtures are presented, along with an analysis of its economic advantages.